Repeated administration of the food additive E171 to mice results in accumulation in intestine and liver and promotes an inflammatory status. Issue 8 (14th September 2019) - Talamini, Laura; Gimondi, Sara; Violatto, Martina B.; Fiordaliso, Fabio; Pedica, Federica; Tran, Ngoc Lan; Sitia, Giovanni; Aureli, Federica; Raggi, Andrea; Nelissen, Inge; Cubadda, Francesco; Bigini, Paolo; et al.
Abstract: Titanium dioxide (TiO2 ) is widely used in pharmaceuticals preparations, cosmetics, and as a food additive (E171). It contains microparticles and a fraction of nanoparticles (NPs) which can be absorbed systemically by humans after ingestion. Increasing concern has been aroused about the impact of oral exposure to TiO2 NPs from dietary and non-dietary sources on human health. In spite of several toxicological studies conducted in recent years, a solid risk assessment of oral exposure to E171 has not been satisfactorily achieved. We investigated whether repeated oral administration of E171 to mice at a dose level (5  mg/kg body weight for 3  days/week for 3  weeks) comparable to estimated human dietary exposure, results in TiO2 deposition in the digestive system and internal organs, and in molecular and cellular alterations associated with an inflammatory response. To reproduce the first phase of digestion, a new administration approach involving the dripping of the E171 suspension into the mouth of mice was applied. Significant accumulation of titanium was observed in the liver and intestine of E171-fed mice; in the latter a threefold increase in the number of TiO2 particles was also measured. Titanium accumulation in liver was associated with necroinflammatory foci containing tissue monocytes/macrophages. Three days after the last dose, increased superoxide production and inflammation were observed in the stomach and intestine. Overall, the present study indicates that the risk for human health associated with dietary exposure to E171 needs to be carefully considered.